Ketorolac versus Metamizol in the treatment of postoperative pain in children - Palo Núñez, Gloria Pamella (2015)
Objective: Evaluate the effectiveness of Ketorolac and Metamizol in the treatment of acute postoperative pain of adenotonsillectomy in children three to six years old receiving medical care in the Department of Anesthesiology at the Hospital Alberto Sabogal Sologur enduring the period 2012-2013. Material and Methods: Observational, descriptive, retrospective and cross-sectional study. The study involved 115 children who under went elective adenotonsillectomy whose ages were between three to six years old. They are according to two groups that received analgesic therapy in the operating room, 58 children received Metamizol and 57 children received Ketorolac. Results: In the group receiving Ketorolac, 56.1% had no pain in the postanesthesic recovery unit according to the scale of Oucher and 43.9% had mild to moderate pain (1-6). The group that received Metamizol, 19% of children reported pain and 74.1% rated their pain from mild to moderate. The degree of pain relief measured Oucher scale was higher in patients receiving Ketorolac (p <0.05). Conclusion: Reducing postoperative pain in adenotonsillectomy in children with Ketorolac is higher than Metamizol.